CYTOKINES FOR THE DIAGNOSIS AND IMMUNOTHERAPY AGAINST BOVINE MASTITIS - Mukherjee, Reena; Sahu , B D (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The study of the bovine cytokine network has been made possible through the production of a wide range of bovine recombinant cytokines and these have been used as a new avenue in mastitis therapy and prophylaxis. Indiscriminate use of antibiotics for the treatment of mastitis, emerging strains of micro-organism resistant to antibiotics and formation of highly complex form of micro-organisms in bovine mammary gland, has prompted the scientists to regulate the mammary defence by immunotherapy through the use of cytokines against bovine mastitis. Studies on the adjuvant activity of interleukin-2 (IL-2) and interferon gamma (IFN-γ) have generated promising results on enhancing the immunity of normal and diseased glands. Cytokines could provide a swift, reliable and highly sensitive means of diagnosis. Cytokines are the signals that dictate immune responses in normal and mastitic udders. Hence, subtle changes in the cytokine network of mammary gland in health and disease could help in detecting early infection and in monitoring the effectiveness of the treatment.
Keywords: Cytokine; Immunotherapy; Interferon gamma; Mastitis